Identification of vaccine candidates against serogroup B meningococcus by whole-genome sequencing. - Pizza, M; Scarlato, V; Masignani, V; Giuliani, M; Aricò, B; Comanducci, M; Jennings, G; Baldi, L; Bartolini, E; Capecchi, B; Galeotti, C; Luzzi, E; et al. (2000)
Neisseria meningitidis is a major cause of bacterial septicemia and meningitis. Sequence variation of surface-exposed proteins and cross-reactivity of the serogroup B capsular polysaccharide with human tissues have hampered efforts to develop a successful vaccine. To overcome these obstacles, the entire genome sequence of a virulent serogroup B strain (MC58) was used to identify vaccine candidates. A total of 350 candidate antigens were expressed in Escherichia coli, purified, and used to immunize mice. The sera allowed the identification of proteins that are surface exposed, that are conserved in sequence across a range of strains, and that induce a bactericidal antibody response, a property known to correlate with vaccine efficacy in humans.